The Octopus and the Other: Capitalocene Contradictions in the Symbolic Order - Gray, Kelly (Journal of Ecohumanism, 2022)
This article exercises a Lacanian psychoanalytic intervention into ecocriticism through examining the contradictions of the Capitalocene within Frank Norrisâ€™s 1901 novel, The Octopus. Drawing upon Jason Mooreâ€™s dialectical framework in the Anthropocene or Capitalocene? Nature, History and the Crisis of Capitalism (2016) and Philip R. Polefroneâ€™s â€œThe Stock Ticker in the Garden: Frank Norris, American Literary Naturalism, and Capitalocene Aestheticsâ€ (2020), this article examines the contradictory naturalization of capitalism in nature within the novelâ€™s depiction of the wheat and railroad industries in California through the ideology of the Capitalocene. This article then analyzes the novelâ€™s pairing of AngÃ©leâ€™s sexual assault with the industrial assault of the land. Read through a psychoanalytic framework, the assaults in the novel together illuminate how the search for the other in the novel effectively obscures the psychoanalytic understanding that â€œthere is no big Other,â€ or the understanding that the Capitalist symbolic order is inherently contradictory.